The Gq signalling pathway inhibits brown and beige adipose tissue - Klepac, Katarina; Kilić, Ana; Gnad, Thorsten; Brown, Loren M.; Herrmann, Beate; Wilderman, Andrea; Balkow, Aileen; Glöde, Anja; Simon, Katharina; Lidell, Martin E.; Betz, Matthias J.; Enerbäck, Sven; et al. (Nature Communications, 2016)
Brown and beige adipose tissues contribute to organismal energy expenditure by generating heat. Here, Klepac et al. survey G protein-coupled receptors in brown fat and show that Gq-coupled receptors inhibit expression of thermogenic proteins in mice and in human adipocytes.